2021
DOI: 10.18433/jpps31586
|View full text |Cite
|
Sign up to set email alerts
|

Growth Hormone Signaling Pathway Leading to the Induction of DNA Synthesis and Proliferation in Primary Cultured Hepatocytes of Adult Rats

Abstract: Background: We investigated the signal transduction pathway associated with growth hormone (GH)-stimulated DNA synthesis and proliferation in primary cultured hepatocytes. Methods: Adult rat hepatocytes were isolated from normal livers by two-step in situ collagenase perfusion to facilitate disaggregation of the adult rat liver. Then hepatocytes were cultured in serum-free Williams’ medium E supplemented with GH (1-100 ng/ml) in the presence or absence of test reagents. GH-induced hepatocyte DNA synthesis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Previous studies and our results show that dairy cows with ketosis have higher blood concentrations of TNF-α, IL-18, and GH (Song et al, 2016;El-Deeb and El-Bahr, 2017;Du et al, 2018), which could activate mTORC1 in a different way (Zhang et al, 2008;El-Darawish et al, 2018;Kimura et al, 2021). In addition, activity of AMP-activated protein kinase, one of the upstream targets of and a negative regulator of mTORC1, was decreased in calf hepatocytes treated with BHB and in mouse hepatocytes treated with FFA (Deng et al, 2016;Xu et al, 2021a).…”
Section: Discussionmentioning
confidence: 47%
“…Previous studies and our results show that dairy cows with ketosis have higher blood concentrations of TNF-α, IL-18, and GH (Song et al, 2016;El-Deeb and El-Bahr, 2017;Du et al, 2018), which could activate mTORC1 in a different way (Zhang et al, 2008;El-Darawish et al, 2018;Kimura et al, 2021). In addition, activity of AMP-activated protein kinase, one of the upstream targets of and a negative regulator of mTORC1, was decreased in calf hepatocytes treated with BHB and in mouse hepatocytes treated with FFA (Deng et al, 2016;Xu et al, 2021a).…”
Section: Discussionmentioning
confidence: 47%
“…GH promotes the autocrine secretion of IGF-I from the hepatocytes via the GH receptor/JAK2/PLC/Ca 2+ pathway. We then found that the secreted IGF-I directly promotes DNA synthesis and hepatocyte proliferation (Figure 5) [15,16,23].…”
Section: Ghmentioning
confidence: 84%
“…We also found that there are many factors that promote hepatocyte proliferation, but there are few factors that can strongly inhibit the effects of these hepatocyte growthpromoting factors (Table 1). Recently, we were also able to confirm the hepatocyte proliferation-promoting effects of 5-HT and growth hormone (GH) in culture [14][15][16][17][18]. Therefore, we investigated the associated intracellular signaling pathways and found that these regulatory factors are indirect mitogens that act via the secretion of autocrine factors (transforming growth factor-α (TGF-α), insulin-like growth factor-I (IGF-I), etc.).…”
Section: Isolation Purification and Primary Culture Of Hepatocytesmentioning
confidence: 99%
“…Rats were anesthetized by intraperitoneal injection of 45 mg/kg sodium pentobarbital. Primary hepatocytes were isolated and enriched by a two-step in situ Seglen procedure 10 , 11 with minor modifications as previously described. 12 Fresh hepatocytes (5.0 × 10 4 cells/cm 2 ) were placed onto 12.5 cm 2 cell culture flasks coated with collagen type II and incubated in Williams’ medium E containing 10% fetal bovine serum.…”
Section: Methodsmentioning
confidence: 99%